THE REALIZATION OF CODE MIXING AND CODE SWITCHING OF INDONESIAN CELEBRITIES' CAPTION ON INSTAGRAM - Tri Indah Rezeki; Rakhmat Wahyudin Sagala (Serunai : Jurnal Ilmiah Ilmu Pendidikan, 2021)
Code mixing and code switching are sociolinguistics phenomenon that occur in a communication process and become trend of language style for Indonesian. Therefore, this research focuses on the realization of code mixing and code switching that emerges on Indonesia celebrities’ caption on Instagram. This research aims to find out analysis of code mixing and code switching realized by Indonesian celebrities on Instagram. Specifically, this research investigated kinds of code mixing and code switching, and the dominant kinds of code mixing and code switching realized by Indonesian celebrities on Instagram. To analyze the data, the researchers transcribed celebrities’ caption on Instagram that contain code mixing and code switching. This research was descriptive qualitative method and collecting the data by utilizing documentation method. This research employed content analysis that focused on analyzing the kinds of code mixing and code switching. The result after analyzing the data, there were 18 code switching and 13 code mixing. The Indonesian celebrities dominantly used external code switching and insertion code mixing on their caption in Instagram. Keywords: Code mixing, code switching, kinds of code mixing, kinds of code switching